A One-Sided Competition Mathematical Model for the Sterile Insect Technique. (30th July 2020) - Ben Dhahbi, Anis; Chargui, Yassine; Boulaaras, Salah Mahmoud; Ben Khalifa, Sana
Abstract : We study a simple mathematical model describing the dynamics of a wild-type pest insects population experiencing competition from sterile insects (one-sided competition). This model can be used for conceiving control strategies based on the Sterile Insect Technique (SIT) or the Incompatible Insect Technique (IIT), aiming to reduce or eradicate Red Palm Weevil (RPW) populations in some target regions. We show that suppression may occur for continuous and periodic release strategies for various intraspecific and interspecific submodels except in the case of a single release strategy where a strong Allee effect is required.